2023
DOI: 10.1055/a-2153-8927
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Contributions to Biliary Atresia: A Developmental Cholangiopathy

Dominick J. Hellen,
Saul J. Karpen

Abstract: Biliary atresia (BA) is the most prevalent serious liver disease of infancy and childhood, and the principal indication for liver transplantation in pediatrics. BA is best considered as an idiopathic panbiliary cholangiopathy characterized by obstruction of bile flow and consequent cholestasis presenting during fetal and perinatal periods. While a number of etiologies have been proposed, each has significant drawbacks that have limited understanding of disease progression and the development of effective treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…Biliary atresia is a major disorder affecting infants and one of the diseases benefiting from liver transplantation [9]. Its etiology is due to the obstruction of bile flow leading to cholangiopathy during fetal and prenatal stages [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biliary atresia is a major disorder affecting infants and one of the diseases benefiting from liver transplantation [9]. Its etiology is due to the obstruction of bile flow leading to cholangiopathy during fetal and prenatal stages [9].…”
Section: Introductionmentioning
confidence: 99%
“…Biliary atresia is a major disorder affecting infants and one of the diseases benefiting from liver transplantation [9]. Its etiology is due to the obstruction of bile flow leading to cholangiopathy during fetal and prenatal stages [9]. Recent studies have identified the role of genetic contributions along with the previously known causes, including viral infections and toxins [9].…”
Section: Introductionmentioning
confidence: 99%